In Vitro Micro-Cutting Of Vanilla (Vanilla Planifolia Andrews.) In Different Naa And Bap - Prabaninggar, Rizki Amalia; Sasmita, Ellen Rosyelina; Wahyurini, Endah (Journal TECHNO, 2021)
Vanilla is one of the spice plant that has a high selling value. The problem with conventional propagation of vanilla by stem cuttings is the attack of stem rot disease caused by Fusarium oxisporum f sp. and limited planting material, therefore can be overcome by tissue culture techniques. This study aims to examine the interaction between the various concentrations of NAA and BAP, obtain the most appropriate concentrations of NAA and BAP for vanilla’s micro-cutting. The study used a Completely Randomized Design (CRD) method. The first factor is the concentration of NAA consisting of N1: 0,5 ppm, N2: 1 ppm, and N3: 1,5 ppm. The second factor is the concentration of BAP consisting of B1: 1 ppm, B2: 2 ppm, and B3: 3 ppm. Observation data were analyzed using Analysis of Variance (ANOVA) and  Duncan's Multiple Range Test (DMRT) at 5% level. The results showed that there was no interaction between the treatment of NAA and BAP concentrations on vanilla micro-cutting. The use of 1 ppm NAA gave the best results on root length. BAP at all concentrations gave the same response on parameters of time to grow buds, live percentage, number of shoots, number of roots, number of leaves, root length, and dry weight of plantlets.